Análise da implementação do Programa Saúde na Escola em um município do Estado de São Paulo - Muñoz, Maria Cristina Muñoz (2019)
The family health teams have as guidelines to establish a close relationship with the population of the regions where they work and together with the education teams in the implementation of the Health in School Program (PSE), can strengthen the union between these two important sectors, concretizing the principle of intersectoriality in the Unified Health System. This research had as general objective to analyze the implementation of the PSE in a municipality of the interior of the state of São Paulo. And as specific objectives, identify the actions of the PSE in the School implemented by the teams of family health and education and analyze the perceptions of health professionals and education regarding the process of implementation of the PSE. It is a study of the identification of actions and perceptions about a given practice, using the precepts of qualitative research. The subjects of the study were 16 health and education professionals in a municipality of the interior of the state of São Paulo. For data collection, we used a documentary survey and individual interviews with professionals through a semi-structured interview script. For the data analysis, the Bardin, content analysis was used, by means of which the following thematic categories were formulated: actions developed in the PSE, the meaning of health promotion in the school, the importance of the PSE and the intersectoriality.In the PSE the results of the research indicate that in most situations, the school seems to open the space so that the health team can carry out actions with students that are already determined by the health sector. There is a consensus on the good relationship that they affirmed to exist between both sectors, but the statements of the professionals also showed that there is a certain role of the health sector as a precursor of the initiatives of the actions implemented in the PSE. To what can be apprehended, there seems to be an easy communication between health and education, but it does not indicate a complete integration, since the health sector already has a previous programming of the actions to be implemented in the school.